2015
DOI: 10.4049/jimmunol.1403133
|View full text |Cite
|
Sign up to set email alerts
|

CD13 Restricts TLR4 Endocytic Signal Transduction in Inflammation

Abstract: Dysregulation of the innate immune response underlies numerous pathological conditions. The Toll-like Receptor 4 (TLR4) is the prototypical sensor of infection or injury that orchestrates the innate response via sequential activation of both cell-surface and endocytic signaling pathways that trigger distinct downstream consequences. CD14 binds and delivers LPS to TLR4 and has been identified as a positive regulator of TLR4 signal transduction. It is logical that negative regulators of this process also exist t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 41 publications
3
63
0
Order By: Relevance
“…Since Fhmuc enhanced the pro-inflammatory effect of LPS on DCs, but did not induce DC maturation itself, we sought to evaluate whether Fhmuc could induce an increase in the expression of TLR4, the main receptor responsible for mediating LPS recognition and engagement of pro-inflammatory signaling pathways leading to activation of the NF-κB transcription factor43334. Thus, we treated BMDCs with Fhmuc followed by LPS, or with Fhmuc or LPS alone and evaluated the kinetics of TLR4 expression by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Since Fhmuc enhanced the pro-inflammatory effect of LPS on DCs, but did not induce DC maturation itself, we sought to evaluate whether Fhmuc could induce an increase in the expression of TLR4, the main receptor responsible for mediating LPS recognition and engagement of pro-inflammatory signaling pathways leading to activation of the NF-κB transcription factor43334. Thus, we treated BMDCs with Fhmuc followed by LPS, or with Fhmuc or LPS alone and evaluated the kinetics of TLR4 expression by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…CD13 is upregulated during LPS stimulation and functions to restrict TRIF signaling, but not myddosome signaling, in DCs and macrophages (Fig. 1A) [27]. CD13-deficient DCs exhibit enhanced TLR4 endocytosis, suggesting its involvement in regulating the endocytic process.…”
Section: Negative Regulation Of Tlr4 Endocytosismentioning
confidence: 99%
“…Exactly how CD13, which binds directly to TLR4, inhibits TLR4 endocytosis remains an open question. The mechanism is not likely to be through inhibition of known TLR4 endocytic determinants such as MD-2 or CD14, as myddosome signaling remains intact in CD13-deficient cells and CD13 does not affect CD14 endocytosis or consistently co-localize with CD14 in endosomes [27]. Importantly, the effects of CD13 on myeloid cells may have consequences in vivo as dysregulation of TRIF signaling results in increased iNOS expression and potentially limits tissue repair during ischemic injury in CD13-deficient mice.…”
Section: Negative Regulation Of Tlr4 Endocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…The SPR data also revealed that β‐AT binds to both CD13 and CD300f with higher affinity than α‐AT. Both of these receptors are known to be negative regulators of inflammatory signaling on monocytes with CD13 playing a role in internalization of Toll‐like receptor 4 (TLR4) and CD300f being involved in blocking both MyD88 and TRIF‐mediated TLR signaling through activation of Src homology region 2 domain‐containing phosphatase 1 (SHP‐1) . Based on these observations, it has been hypothesized that β‐AT contributes to modulation of innate immune responses during infection.…”
Section: Anti‐inflammatory Receptors For β‐At On Monocytesmentioning
confidence: 99%